2013
DOI: 10.1002/marc.201300696
|View full text |Cite
|
Sign up to set email alerts
|

Epoxides as Reducing Agents for Low‐Catalyst‐Concentration Atom Transfer Radical Polymerization

Abstract: Activators regenerated by electron transfer atom transfer radical polymerization (ARGET ATRP) conditions utilizing a low concentration of catalyst are successfully applied for the preparation of well-defined poly(glycidyl methacrylate) without the addition of external reducing agents. The living character of polymerization is evidenced by successful chain extensions with methyl methacrylate and methyl acrylate, again, in the absence of additional reducing agents, yielding block copolymers. The epoxide groups i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 40 publications
4
40
0
Order By: Relevance
“…This possibility may be prevented by treatment of the catalyst with a reducing agent to regenerate it for further ATRPs. For example, light, or reducing agents such as tin 2‐ethylhexanoate, ascorbic acid, methylaluminoxane, alcohols, triphenylphosphine and epoxides react with the oxidatively stable Cu(II) complex and generate the activator. Reusing an identical catalyst for five successive trials resulted in approximately 50% conversion at each polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…This possibility may be prevented by treatment of the catalyst with a reducing agent to regenerate it for further ATRPs. For example, light, or reducing agents such as tin 2‐ethylhexanoate, ascorbic acid, methylaluminoxane, alcohols, triphenylphosphine and epoxides react with the oxidatively stable Cu(II) complex and generate the activator. Reusing an identical catalyst for five successive trials resulted in approximately 50% conversion at each polymerization.…”
Section: Resultsmentioning
confidence: 99%
“…It was recently demonstrated that epoxides can act as reducing agents in low-catalyst concentration ATRP reactions (Scheme 2) (50,57), and in the chain extension reactions reported here, the epoxides present in the macroinitiator served to regenerate the lower oxidation state metal complex (activator) via reduction of the higher oxidation state deactivator.…”
Section: Chain Extension Of Hb-polygma-br X Via Low-catalyst Concentrmentioning
confidence: 96%
“…Linear polyGMA was synthesized using low-catalyst concentration ATRP without external reducing agent (DP n,targ = 200) as previously reported (50). Dried polyGMA (100 mg, 70.3 μmol epoxide groups) was weighed into a small test tube equipped with a magnetic stir bar and dissolved with 0.5 mL DMSO-d 6 .…”
Section: Modification Of Polygma With Different Tertiary Aminesmentioning
confidence: 99%
“…TPMA is a widely used ligand for copper catalyzed ATRP methods ranging from conventional ATRP (41,42,102) to improved protocols that require only ppm amounts of the catalyst (13,40,49,(55)(56)(57)(58)(103)(104)(105)(106). These enhanced synthetic procedures allow for the use of air stable Cu II complexes, often eliminating the need for deoxygenation, and rely on the continuous reduction of Cu II to Cu I species within the polymerization process.…”
Section: Applications In Atrpmentioning
confidence: 99%